Automotive workers: the role of coordinative and conditional abilities as effectiveness wellness indicator - Angelo Rodio; Tommaso Di Libero; Alessandro Biffi; Fredrick Fernando; Luigi Fattorini (Frontiers Media S.A., 2024)
IntroductionNoncommunicable diseases are on the rise due to sedentary and unhealthy lifestyles. The World Health Organization (WHO) and the American College of Sports Medicine (ACSM) recommend maintaining a healthy diet and engaging in regular physical activity, particularly in the workplace. Prolonged and repetitive work tasks can result in extended sick leave and decreased productivity while at work. Therefore, it is important to identify predictive factors that can act as indicators of the health status of employees. Utilizing motor abilities assessment tests can help to identify health issues at an early stage. Promoting preventive health measures is crucial for addressing chronic diseases and enhancing overall occupational well-being. The purpose of the study was to characterize workers' motor abilities and fitness levels and identify potential indicators.MethodsA total of 605 workers participated in this study, including 529 male participants with a height of 176 ± 0.09 cm and a body mass of 75.9 ± 14.1 kg and 77 female participants with a height of 162 ± 0.11 cm and an average body mass of 58.9 ± 11.1 kg. These individuals were enrolled during an Italian automotive corporation's mandatory annual medical check-up. The participants were categorized into three groups based on their occupational roles: blue-collar, manager, and white-collar groups. The participants underwent motor abilities assessment tests for upper-limb strength, trunk flexibility, and reaction time.ResultsThe blue-collar group reported the best results in upper-limb strength (93.3 kgf ± 18.60), but had the worst results in flexibility (21.7 cm ± 7.90), total reaction time (58.8 s ± 4.74); and average intermedium (0.68 ms ± 0.11). The white-collar group reported the best result in flexibility (23.7 cm ± 8.94) and reaction time (48.5 s ± 4.38; 0.64 ms ± 0.09).ConclusionDespite being frequently used to assess health status, handgrip measurements may not provide accurate differentiations because of the common use of blue-collar workers for tasks that require upper-limb strength. In contrast, reaction time metrics appear more reliable and discriminative in evaluating a worker's physical fitness.